Co-morbilidad en casos nuevos de tuberculosis pulmonar con bacilo de koch positivo (BK+), zona 7 - Ecuador - Astudillo Lalangui, María José (2014)
The research called "Co-Morbidity in New cases of pulmonary tuberculosis with bacillus Koch positive (Bk+) Ecuador-zone 7, as part of Macroproyect” Bacteriological conversion, associated to co-morbidity, delivery service and attitude of patients, in new cases of pulmonary tuberculosis Bk+. Ecuador zone 7 ", whose main objective is to identify the co-morbidity in new cases of pulmonary tuberculosis Bk+ Ecuador – zone 7 : The study is framed in the field of descriptive research, retrospective and prospective in a sample of diagnosed new cases with pulmonary tuberculosis Bk+ and the identified cases receiving antifimic treatment during the investigation, the information was obtained through the startup form of the diagnosed patient with TBP BK + , which instrument was a guide in which be known diseases associated with pulmonary tuberculosis. As a result a total of two hundred seventy one new cases of pulmonary tuberculosis identified; (Tbp) BK + in the zone 7 Ecuador in 2013, considering that the comorbidity with more people is located in the province of El Oro, associated with the following pathologies in the following order, Diabetes, malnutrition, alcoholism, VIH / SIDA, smoking and drug addiction, predominating in males in the young adult people of thirty to fifty years old, belonging to the provinces of the zone seven-Ecuador in 2013. Keywords: Pulmonary tuberculosis BK+; Diabetes, Smoking; alcoholism; Addiction.